Rethinking Market Discipline in Banking : Lessons from the Financial Crisis - Stephanou, Constantinos (2012)
The main objective of this paper is to rethink the use of market discipline for prudential purposes in light of lessons from the financial crisis. The paper develops the main building blocks of a market discipline framework, and argues for the need to take an expansive view of the concept. It also illustrates using actual bank case studies from the United States its apparent failures in the crisis, particularly the failure to prevent the buildup of systemic, as opposed to idiosyncratic, risks. However, while the role of market discipline in the design of macro-prudential regulation appears to be largely constrained, more can be done on the micro-prudential side to promote clearer market signals of bank riskiness and to encourage their use in the supervisory process.